Pigmented villonodular synovitis of hip diagnosed with hip arthroscopy - (:unkn) unknown (SPRINGER, 2007)
Pigmented villonodular synovitis is a synovial proliferative disorder that rarely involves the hip joint. It is an inflammatory response to an unknown agent. Pigmented villonodular synovitis of the hip usually presents with extensive joint destruction because of the limited joint space. Various methods of treatment modalities including synovectomy, total hip arthroplasty, radiation therapy and arthrodesis were used for treating this disease in hip joint. Diagnosis and treatment with hip arthroscopy is a new and less invasive modality comparing to open procedures.
Keywords: pigmented villonodular synovitis; cartilage; hip; arthroscopy; synovectomy